Optimal sizing and techno-enviro-economic feasibility assessment of large-scale reverse osmosis desalination powered with hybrid renewable energy sources. (15th November 2020) - Elmaadawy, Khaled; Kotb, Kotb M.; Elkadeem, M.R.; Sharshir, Swellam W.; Dán, András; Moawad, Ahmed; Liu, Bingchuan
Highlights: Large-scale reverse osmosis desalination powered by hybrid renewable energy source. The optimal off-grid power system was photovoltaics/wind/diesel/battery/convertor. The emitted carbon dioxide of the optimal system outperformed diesel system by 81.5%. Energy storage systems are required to meet the energy demand during night times. Abstract: Seawater desalination is a viable source of potable water, particularly for the coastal and remote areas. However, their sustainability is limited by the intensive energy demand of the present methods. Renewable energy is an inexhaustible source of energy, accompanied by cost reduction benefits and clean power generations. Seawater desalination powered with renewable energy sources is being attractive, mainly if the utility-grid is absent. This paper aims to design a renewable energy system, to meet the electrical load demand of large-scale reverse osmosis desalination plant (1500 m 3 /d), and to find the optimal sizing and techno-economic and environmental feasibility assessment of several off-grid power systems. Two off-grid scenarios with different combinations of hybrid power systems were proposed and compared with the base-case of diesel. The first scenario consists of a photovoltaic, wind turbine, diesel, and generator, while the second scenario is equipped with battery storage devices. A total of eleven hybrid renewable energy systems were modelled, analyzed, and compared with the aid of HOMER Pro software to identify the best performance and the optimal plan configuration. The optimization results show that the proposed photovoltaic/wind/diesel/battery/convertor system outperformed the other alternatives and exhibited reduction potential of 60.7%, 73.7%, 62% and 81.5% lower than the existing diesel with regards to the net present cost, renewable fraction, cost of energy, and carbon dioxide emission, respectively. The optimum case consists of 451 kW solar panels, 25 wind turbines, 250 kW diesel power, battery storage of 352 string, and 358 kW system converter. The results obtained by the optimal plan with low cost and environmental protection aspects would provide a new sight for real field applications of large scales reverse osmosis applications.